(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
في دراستنا الحالية وعلى مدى خمس سنوات من 2003-1998 تم البحث في أسباب فشل عمليات التحصين المتكررة ضد مرض التهاب الجراب المعدي المنفذة في مزارع رعاية الفرُّوج, وعند إجراء الفحوص اللازمة لعينات الأمصال الدموية في اختبار الترسيب الانتشاري في الغراء الهلامي وبمتابعة تدابير التلقيح وتجنب الأخطاء الشائعة ومناقشتها والنتائج مع معطيات المصادر توصلنا إلى: 1- تلقيح الصيصان الناتجة عن أمات محصنة ضد المرض لأول مرة بعمر 12 يوم يعطي استجابة مناعية إيجابية، ظهرت بمعيار أضداد وصل إلى 6Log2 وبنسبة بلغت 95%، وإعادة التلقيح بعمر 26-24 يوم يوفران الحماية الفعالة للطيور ضد المرض. 2- استخدام لقاحات محضَّرة من ذرية متوسطة ومتوسطة قوية الفوعة ومضعَّفة (plus) وبجرعة زائدة قليلاً مع حساب حيِّز الفقد في الأنابيب لتعويض النقص المحتمل يعطي نتائج إيجابية في الوقاية من خطر الإصابة بالفيروس الحقلي شديد الفوعة. 3- إتباع الإجراءات الصحيحة وتجنب الأخطاء الشائعة عند إعطاء اللقاح مع مياه الشرب والمتعلقة بمدة التعطيش3-2 ساعة المتوافقة مع الإضاءة والفصل، وبالكمية المحددة تبعاً للعمر، وبالنوعية العذبة الخالية من المطهرات والشوائب والمعقمة بالغليان والمبرَّدة والمضاف إليها مسحوق الحليب خالي الدسم بكمية 2غ/ل، والموزعة بأعداد كافية من المناهل تحفز الطيور على تناول محلول اللقاح بسرعة وبالجرعة الكافية وتطيل فترة احتفاظ اللقاح بحيويته وبالتالي قدرته على تحفيز الأجهزة المناعية في الجسم وتشكيل الأضداد اللازمة لحماية الطير من خطر الإصابة بالمرض. The present study was done chicken farms during the period between 1998 and 2003, during which an investigation into the causes of the recurring failure of vaccination measures against bursal disease infection. Agar gel testing and observation of vaccination measures so as to discuss and avoid common mistakes, as well as the discussion of results and comparing them with references, have all led to the following conclusions: 1-Frst time vaccination of 12 days old broilers resulting from maters with maternal antibody has positive immunization result, as shown in antibodies liter 6log2 and in percentage terms 95%. Repeating the vaccination when the boiters are 24-26 days old ensures protection of children against the disease. 2- Using vaccines prepared from moderate strain in the first time and a less strong strain (plus) in the second time with an additional dose taking in consideration the lost water in the tubes. give appositive vaccinations. 3- The application of the right measures during vaccination in drinking water connected with a thirsty period 2-3 hourS compatible with lighting system and season, in a specific quantity according the age, with a clean water without disinfectants sterilized by boiling and cooling AND adding a milk powder without fat in a dose 2g/L, distributed in a sufficient drinking places. stimulate broilers to take the vaccine in a sufficient speed and dose, that prolong the vitality of the vaccine and its power in stimulating immunity system in the body and forming the antibodies that protecting the broiler from the disease.